Contribution de la motivation en éducation physique sur la pratique d’activités physiques : comparaison entre classes spéciales et classes ordinaires - Blais, Dominique; Girard, Stéphanie; Lemoyne, Jean (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
This study examines the contribution of the goals pursued in physical education to the practice of leisure-time physical activity (LTPA) among high school students (N = 277) according to class type (regular or special education). Path analysis revealed positive relationships between LTPA and the students’ attitudes and their perceived competence (PC). Their attitudes were positively associated with mastery climate, PC, and mastery goals, and negatively associated with performance-avoidance goals. Invariance analyses revealed that the model was statistically invariant for both types of classes. This research supports the importance of motivational climate as a determinant of students’ predispositions to be active outside of physical education classes. Keywords: motivational climate, achievement goals, perceived competence, special education, invariance